Mary, Bloody Mary - Meyer, Carolyn; Book 1 (New York, NY Scholastic, Inc., 1999)
Mary Tudor, who would reign briefly as Queen of England during the mid sixteenth century, tells the story of her troubled childhood as daughter of King Henry VIII.
87274
Keywords: Mary I, Queen of England -- Childhood and youth -- Fiction; Kings and rulers -- Fiction; Great Britain -- History -- Mary I, 1553-1558 -- Fiction